2020
DOI: 10.1080/15548627.2020.1816342
|View full text |Cite
|
Sign up to set email alerts
|

Keratinocyte autophagy enables the activation of keratinocytes and fibroblastsand facilitates wound healing

Abstract: Macroautophagy/autophagy is a cellular catabolic process that is implicated in several physiological and pathological processes. However, the role of epidermal autophagy in wound healing remains unknown.Here, using mice with genetic ablation of the essential Atg5 (autophagy related 5) or Atg7 (autophagy related 7) in their epidermis to inhibit autophagy, we show that keratinocyte autophagy regulates wound healing in mice. Wounding induces the expression of autophagy genes in mouse skin. Epidermisspecific autop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(99 citation statements)
references
References 56 publications
2
96
1
Order By: Relevance
“…Such that, ATG7 regulates ultraviolet-induced cytokine expression and secretion, which can promote COX-2 expression in keratinocytes in a CREB1/CREB-dependent and IL1β-dependent manners 74 . In addition, autophagy promotes CCL2 transcription in epidermal keratinocytes through the AMPK-BRAF-MAPK1/3/ERK-activator protein 1 (AP1) pathway 75 , and upregulates CXCL8 to trigger mesenchymal stem cell-mediated CD4 + T cell migration and differentiation 76 . The presence of microbes in the uterine cavity has been widely demonstrated, which initiates immunologic reactions 77 .…”
Section: The Estrogen / Progesterone-autophagy-immunity Axis In Menstmentioning
confidence: 99%
“…Such that, ATG7 regulates ultraviolet-induced cytokine expression and secretion, which can promote COX-2 expression in keratinocytes in a CREB1/CREB-dependent and IL1β-dependent manners 74 . In addition, autophagy promotes CCL2 transcription in epidermal keratinocytes through the AMPK-BRAF-MAPK1/3/ERK-activator protein 1 (AP1) pathway 75 , and upregulates CXCL8 to trigger mesenchymal stem cell-mediated CD4 + T cell migration and differentiation 76 . The presence of microbes in the uterine cavity has been widely demonstrated, which initiates immunologic reactions 77 .…”
Section: The Estrogen / Progesterone-autophagy-immunity Axis In Menstmentioning
confidence: 99%
“…34 Tian et al 35 found that progranulin (PGRN), a glycoprotein highly expressed by various cells and involved in various pathophysiological processes including wound repair and inflammation, is upregulated in psoriatic lesions and can suppress inflammation in keratinocytes by promoting autophagy through the Wnt/β-catenin signal pathway. Qiang et al 36 demonstrated that tumor necrosis factor (TNF) and wounding can induce autophagic flux and autophagy-related gene expression through the nuclear factor (NF)-κB signaling pathway in epidermal keratinocytes. On the contrary, Chikh et al 37 reported that iASPP protein can negatively modulate autophagy in keratinocytes by inhibiting the interaction between Atg5-Atg12 and Atg16L1.…”
Section: Autophagy In K Er Atino C Y Te S and S K In Barriermentioning
confidence: 99%
“…Lee et al 41 found that autophagy can suppress skin inflammation by reducing the expression of polyubiquitinated protein p62 which positively regulates the production of inflammatory cytokines. Intriguingly, Qiang et al 36 showed that autophagy facilitates skin wound healing by coordinating keratinocyte-fibroblast interaction. An et al 42 demonstrated that autophagy induces the secretion of vascular endothelial growth factor in mesenchymal stem cells and promotes skin healing and tissue regeneration.…”
Section: Autophagy In K Er Atino C Y Te S and S K In Barriermentioning
confidence: 99%
“…Wounding mouse skin induces the expression of autophagy genes in the epidermis and some of these genes (Atg5 or Atg7) are needed for proper wound closure, infiltration by immune cells, and for the production of cytokine CCL2. Applying recombinant CCL2 can reverse the effect of impaired autophagy indicating that the main role of autophagy in this context is to promote wound healing by inducing the production of CCL2 11 . In rats, elevated autophagy at the wound margin is required for clearance of bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Wounding has been shown in Drosophila, planarians, zebrafish, rat, mouse and plants to induce autophagy 1,[6][7][8][9][10][11][12] . In plants, rats and mice, autophagy is in turn necessary for efficient wound healing.…”
Section: Introductionmentioning
confidence: 99%